Anti-tumor immunity induced by a novel nanoparticulate vaccine : a mechanistic approach - Zupančič, Eva, 1984- (2016)
Tese de doutoramento, Farmácia (Tecnologia Farmacêutica), Universidade de Lisboa, Faculdade de Farmácia, 2016